STRUKTUR KEPEMILIKAN, DEWAN KOMISARIS, DAN PENGUNGKAPAN PENGENDALIAN INTERNAL - Ivan Krisna Priantaka; Totok Dewayanto (Diponegoro Journal of Accounting, 2019)
The purpose of this study is to examine the effect of managerial ownership, institutional ownership, board of commissioners size, board of commissioners independence, and the number of board of commissioners meetings as independent variables on internal control disclosure as the dependent variable. This study uses company size as a control variable. This study uses secondary data obtained from the Indonesia Stock Exchange (IDX). This study used a sample of 226 manufacturing companies listed on the Indonesia Stock Exchange in the period 2016 - 2017. The method used in this study was purposive sampling. The statistical technique used in this study is multiple linear regression. The results obtained from this study indicate that institutional ownership, board of commissioners size, board of commissioners independence, and the number of board of commissioners meetings have positive and significant effects on internal control disclosure. Managerial ownership does not have a significant effect on internal control disclosure.